2023
DOI: 10.2166/wst.2023.023
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary treatment of coke-oven wastewater using suspended and immobilized whole live cells of constructed bacterial–microalgal consortium: modeling and optimization using ANN–GA hybrid methodology

Abstract: Coke-oven wastewater (CW), containing an array of toxic pollutants above permissible limits even after conventional primary and secondary treatment, needs a tertiary (polishing) step to meet the statutory limit. In the present study, a suitable bacterial–microalgal consortium (Culture C) was constructed using bacterial (Culture B: Bacillus sp. NITD 19) and microalgal (Culture A: a consortium of Chlorella sp. and Synechococcus sp.) cultures at different ratios (v/v) and the potential of these cultures for terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Various growth systems have been analysed to determine the working effectiveness of a mixed culture including a biofilm and immersion system, on the disrupting nature of microalgal cell walls by bacteria. This has raised a prompt research question on whether it could be used as a harvesting technique to extract the nutrients inside the bacterial cell wall (Rai et al, 2023). The bacteria also act as scavengers and consume the dead microalgae and other contaminants within the consortia (Vishwakarma et al, 2022).…”
Section: Microalgae-bacteria Consortiamentioning
confidence: 99%
See 1 more Smart Citation
“…Various growth systems have been analysed to determine the working effectiveness of a mixed culture including a biofilm and immersion system, on the disrupting nature of microalgal cell walls by bacteria. This has raised a prompt research question on whether it could be used as a harvesting technique to extract the nutrients inside the bacterial cell wall (Rai et al, 2023). The bacteria also act as scavengers and consume the dead microalgae and other contaminants within the consortia (Vishwakarma et al, 2022).…”
Section: Microalgae-bacteria Consortiamentioning
confidence: 99%
“…It has been found that the artificial polyculture system produced a higher percentage (60%) of biomass than the naturally constructed system. The tolerance of stress conditions was found to be higher in artificial pond systems than in the natural system (Rai et al, 2023).…”
Section: Binary Culture Of Microalgae In Wastewatermentioning
confidence: 99%